PROSEDUR HUKUM YANG HARUS DITEMPUH PERSEROAN TERBATAS DALAM HAL TERJADINYA PENGURANGAN JUMLAH PENDIRI DAN AKIBAT HUKUMNYA - Sarasvita, Dely Bunga; Wiryawan, I Wayan; Rudy, I Dewa Gede (Kertha Desa; Vol. 01, No. 01, Maret 2013)
Limited Liability Company established under the agreement, it is in accordance with the provisions of Article number 7 (1) Company Law of 2007. In practice frequently encountered condition which the founders of the Company to be less than two (2) peoples, that serves as the sole shareholder. For this condition, the Company shall immediately transfer the shares or issuing new shares to others, to cope the situation. This is in accordance with the provisions of Article 7, paragraph (5) the Company Law of 2007. Legal consequences to the Company that do not adjust as provisions in the Article is losing its status as a legal entity. And after a request from a third party, it will be the dissolution of the Company by the District Court.
Keywords: Limited Liability Company, Sole Transfer, The Sole Shareholder